In vivo imaging of fluorescent single-walled carbon nanotubes within C. elegans nematodes in the near-infrared window - Adi Hendler-Neumark (Elsevier, 2021)
Caenorhabditis elegans (C. elegans) nematodes serve as a model organism for eukaryotes, especially due to their genetic similarity. Although they have many advantages like their small size and transparency, their autofluorescence in the entire visible wavelength range poses a challenge for imaging and tracking fluorescent proteins or dyes using standard fluorescence microscopy. Herein, near-infrared (NIR) fluorescent single-walled carbon nanotubes (SWCNTs) are utilized for in vivo imaging within the gastrointestinal track of C. elegans. The SWCNTs are biocompatible, and do not affect the worms’ viability nor their reproduction ability. The worms do not show any autofluorescence in the NIR range, thus enabling the spectral separation between the SWCNT NIR fluorescence and the strong autofluorescence of the worm gut granules. The worms are fed with ssDNA-SWCNT which are visualized mainly in the intestine lumen. The NIR fluorescence is used in vivo to track the contraction and relaxation in the area of the pharyngeal valve at the anterior of the terminal bulb. These biocompatible, non-photobleaching, NIR fluorescent nanoparticles can advance in vivo imaging and tracking within C. elegans and other small model organisms by overcoming the signal-to-noise challenge stemming from the wide-range visible autofluorescence.